Propuesta de plan de seguridad y salud ocupacional en la Escuela de conducción RODAR - Rodríguez Castillo, Andy Rafael (2024)
Every company should have as its main objective to ensure the well-being, health and working conditions of each employee under its responsibility. Unfortunately, at the Rodar driving school there is no occupational health and safety plan that provides protection, security and comprehensive care for its employees to better perform their jobs, generating greater productivity for the company. It has not identified the physical, mechanical, ergonomic, biological, chemical, psychosocial and environmental risks that its employees and students are exposed to, they have not been assigned the degree of impact that these risks may have on their health, it lacks a person responsible for safety and occupational health, a doctor and internal regulations, omitting a series of activities aimed at preventing occupational risks, which prevents knowing with certainty the impact that work has on the health of its collaborators. Likewise, you cannot track and evaluate risks and update them when necessary because the risks are not defined. It does not prepare an annual report related to its safety and hygiene, it omits an annual training plan in the Single Labor System (SUT) of the Ministry of Labor, nor does it have a record of health inspections carried out at the school by the ANT. The most relevant thing that Rodar has carried out is to carry out first aid courses regarding traffic accidents, training aimed at workers, employees, students and the community in general, it has informative/preventive signage for the company's facilities, and Through the curriculum, it deeply analyzes the various rules and regulations that must govern a driver/student, to avoid traffic accidents, it also has a first aid kit, issues reports to the National Transit Agency on the activities carried out in a certain period taking into account the regulations that non-professional driving schools have. It has a fire extinguisher displayed in a visible and easily accessible place, it has drinking water services for consumption by workers as well as toilets, toilets and urinals in good condition, separating men and women as required by law. To counteract natural threats and anthropogenic risks, Rodar has emergency doors in case of natural disasters.